Approaches to notation in music for piano and live electronics: the performer’s perspective - Pestova, Xenia (Routledge, 2017)
This chapter examines elements of notation in music for piano and live electronics. The author introduces examples from the repertoire and discusses different notational approaches. These are grouped into three main categories. 1 Graphic notations and visual representations or descriptive scores (Boorman 2001) are commonly used in repertoire with fixed media to simplify synchronisation and can also be found in more recent repertoire with interactive live electronics. 2 Tablature-style notations, or prescriptive scores (Boorman 2001) including notation as documentation, offer a different and potentially complementary approach. 3 Hybrid combinations of approaches and notations, including semi-improvised pieces and notation for new instruments, show new perspectives in the field. The author addresses performance practice challenges and draws conclusions from that perspective.